Medieval clothing and textiles, Volume 8 - Netherton, Robin; Owen-Crocker, Gale R. (Boydell & Brewer, 2011)
This volume continues the series' tradition of bringing together work on clothing and textiles from across Europe. It has a strong focus on gold: subjects include sixth-century German burials containing sumptuous jewellery and bands brocaded with gold; the textual evidence for recycling such gold borders and bands in the later Anglo-Saxon period; and a semantic classification of words relating to gold in multi-lingual medieval Britain. It also rescues significant archaeological textiles from obscurity: there is a discussion of early medieval headdresses from The Netherlands, and an examination of a fifteenth-century Italian cushion, an early example of piecework. Finally, uses of dress and textiles in literature are explored in a survey of the Welsh Mabinogion and Jean Renart's Roman de la Rose. Robin Netherton is a professional editor and a researcher/lecturer on the interpretation of medieval European dress; Gale R. Owen-Crocker is Professor of Anglo-Saxon Culture at the University of Manchester. Contributors: Brigitte Haas-Gebhard, Britt Nowak-Böck, Maren Clegg Hyer, Louise Sylvester, Chrystel Brandenburgh, Lisa Evans, Patricia Williams, Katherine Talarico